Manual de micropropagación del yacón (Smallanthus sonchifolius (Poepp. & Endl.) H. Robinson) - Cabrera Pintado, Rosa María; Aliaga Cóndor, Jérica Danae (Instituto Nacional de Innovación Agraria, 2020)
19 Páginas